The effect of individual telerehabilitation on postural stability in people with multiple sclerosis, a pilot study - Grosserová, Barbora; Janatová, Markéta; Horáková, Dana; Novotná, Klára (Studia sportiva, 2024)
Background: The aim of our pilot study was to assess the feasibility and effectiveness of individual balance telerehabilitation for people with multiple sclerosis (MS). Methods: In this pilot study 20 individuals with MS with balance impairment were included (10 in experimental, 10 in control group). The experimental group underwent 12 weeks of individual telerehabilitation (with direct synchronous contact between the physiotherapist and the patient). The control group received conventional outpatient physiotherapy. The standardized tests of balance and functional mobility were assessed at baseline and after intervention. Results: Comparing the two groups, the experimental group achieved statistically significant improvement in balance: the BBS test (p=0.002), TUG (p=0.048), functional test standing on one limb (p=0.01), and subjectively perceived balance with the ABC Scale questionnaire (p=0.041). The substantive significance (Cohen's d) when comparing the two groups reached a large effect size in the BBS (d=0.83) and standing on one limb (d=1.06) and in the MSWS-12 (d=0.78) and ABC Scale questionnaire (d=0.78). Conclusion: Telerehabilitation interventions represent an increasing trend and our data suggest that individually delivered online telerehabilitation can be effective in the treatment of balance and functional mobility disorders in MS.